Chromophobe renal cell carcinoma with metastatic progression and cabozantinib-induced hand-foot syndrome - Esmez, Omer; Esmez, Merve Yildiz; Deniz, Gulnihal (Bmj Publishing Group, 2025)
Renal cell carcinoma (RCC) comprises a heterogeneous group of neoplasms with variable prognoses. Chromophobe RCC, a relatively uncommon subtype, generally follows an indolent clinical course but may occasionally exhibit aggressive or metastatic behaviour. This report describes a woman in the mid 60s with a history of partial nephrectomy for chromophobe RCC who subsequently developed metastatic disease. Systemic treatment with cabozantinib was initiated, resulting in dermatological toxicity. Serial imaging over 4 years demonstrated progressive metastatic involvement, including hepatic lesions. This account underscores the challenges of managing metastatic chromophobe RCC, differentiating true recurrence from potential second primary malignancies and addressing the adverse effects of targeted therapies such as cabozantinib.
Keywords: Renal system; Skin; Urological cancer